Water-soluble small-molecule probes for RNA based on a two-photon fluorescence "off–on" process: systematic analysis in live cell imaging and understanding of structure–activity relationships. Issue 99 (29th November 2017) - Li, Hong; Li, Yuncang; Zhang, Huihui; Xu, Guoyong; Zhang, Yuliang; Liu, Xiaohu; Zhou, Hongping; Yang, Xingyuan; Zhang, Xuanjun; Tian, Yupeng
Abstract : The remarkable two-photon fluorescence responses in vitro and in vivo ofL1–5 for RNA revealed the synergistic effect of the amino group and the pyridinium cation. Abstract : The conveniently obtained water-soluble small-moleculeL1–5 were selective for RNA with remarkable "off–on" two-photon fluorescence responses in vitro and in vivo, showing thatL1–5 can surprisingly stain mitochondria or nucleoli individually with orange fluorescence under different focal lengths. CompoundsL6–8 were prepared, for comparison, to further explore the mechanism of the binding ofL1–5 with RNA, which revealed that the synergistic effect of the amino group and the pyridinium cation played a significant role in distinct cell imaging.